The decline in attitudes toward physician-nurse collaboration from medical school to residency. Issue 3 (3rd May 2020) - Kempner, Samantha; Brackmann, Melissa; Kobernik, Emily; Skinner, Bethany; Bollinger, Megan; Hammoud, Maya; Morgan, Helen
ABSTRACT: While interprofessional collaboration is a critical aspect of optimal patient care, practicing physicians often have sub-optimal attitudes regarding the importance of collaboration with their nursing colleagues. The impact of clinical training on medical students' and residents' attitudes toward physician-nurse collaboration has not been investigated. The primary goal of our study was to examine if learners at different stages in their medical training had more or less favorable attitudes regarding interprofessional collaboration (IPC). A secondary goal was to compare residents in procedural versus non-procedural specialties to determine if attitudes toward IPC varied by specialty type. Third-year medical students and residents at a large public university completed the Jefferson Scale of Attitudes Toward Physician-Nurse Collaboration. Student (n = 129) and resident (n = 292) scores were compared using Student's t-tests. Resident responses were further analyzed by specialty type. Students' perceptions of the physician-nurse relationship were significantly more favorable than the views of residents, particularly in the "Authority" and "Responsibility" domains. Residents in procedural specialties had less favorable attitudes toward physician-nurse collaboration than those in non-procedural specialties. Our findings highlight the importance of developing effective interventions for improving interprofessional collaboration during medical training.